Biophysical, structural, and functional studies of histone binding proteins - Sudhoff, Keely B., author; Luger, Karolin, advisor; Chen, Chaoping, committee member; Henry, Charles, committee member; Woody, Robert, committee member; Hansen, Jeffrey C., committee member (Colorado State University. Libraries, 2010)
Eukaryotic genomes are extensively compacted with an equal amount of histone proteins to form chromatin. A high level of control over chromatin structure is required to regulate critical cellular processes such as DNA replication, repair, and transcription. To achieve this feat, cells have developed a variety of means to locally or globally modulate chromatin structure. This can involve covalent modification of histones, the incorporation of histone variants, remodeling by ATP-dependent remodeling enzymes, histone chaperone-mediated assembly/disassembly, or any combination of the above activities. To understand how chromatin structure is affected by histones, it is essential to characterize the interactions between histones and their associated proteins. In Saccharomyces cerevisiae, the multi-subunit SWR1 complex mediates histone variant H2A.Z incorporation. Swc2 (Swr1 complex 2) is a key member of the SWR1 complex and is essential for binding and transfer of H2A.Z. Chz1 (Chaperone for H2A.Z/H2B) can deliver H2A.Z/H2B heterodimers to the SWR1 complex in vitro. Swc2 1-179 (a domain of Swc2 that retains histone binding and the apparent preference for variant dimers) and Chz1 are intrinsically disordered, but become more ordered upon interaction with histones. Quantitative measurements done under physiological in vitro conditions demonstrate that Chz1 and Swc2 1-179 are not histone variant-specific. They bind to histones with an affinity lower than that of previously described histone chaperones, and lack the ability to act on nucleosomes or other histone-DNA complexes. Small-angle X-ray scattering demonstrates that the intrinsic disorder of the proteins allows them to adopt a multitude of structural states, perhaps facilitating many different interactions and functions. We show that Swc2 1-179, despite its overall acidic charge, can bind double stranded DNA, in particular, 3-way and 4-way junction DNA. These junctions are thought to mimic the central intermediates found in DNA damage repair. This characteristic is unique to Swc2 1-179. Consistent with this unexpected activity, yeast phenotypic assays have revealed a role for SWC2 in DNA damage repair, as indicated by sensitivity to DNA damaging agent methane methylsulfonate. Importantly, our data has exposed a novel role for Swc2 in DNA damage repair. In an independent study, we investigated the histone chaperone Vps75, a Nap1 homolog. Rtt109 is a histone acetyltransferase that requires a histone chaperone for the acetylation of histone H3 at lysine 56 (H3K56). Rtt109 forms a complex with the chaperone Vps75 in vivo and is implicated in DNA replication and repair. We show that deletion of VPS75 results in dramatic and diverse mutant phenotypes, in contrast to the lack of effects observed for the deletion of NAP1. The flexible C-terminal domain of Vps75 is important for the in vivo functions of Vps75 and modulates Rtt109 activity in vitro. Our data highlight the functional specificity of Vps75 in Rtt109 activation.
Keywords: Vps75; Swc2; histone; H2A.Z; Chz1; chaperone; Chromatin; Histones; DNA replication; Protein binding